Transition prospects to sustainable development of the Kamchatka Krai in the Russian Federation - M. Yu. Dyakov (Управление)
The transition to sustainable development remains an urgent task both at the national and regional levels. For the regions of the Far East in Russia this issue is of particular relevance due to the high amount of natural capital they have and the vulnerability of local ecosystems. In the article on the example of one of the regions of the Far East (Kamchatka Krai) possible directions for the transition to a model of sustainable and balanced development are identified. The purpose of this study is to evaluate alternatives for such a transition using simulation tools. In the course of the work a characteristic of the region was presented with the main components’ assessment of natural, human and physical capital. At the same time the definition of a complex regional balance is formulated as a regional projection of sustainability and a space of opportunities for the optimal use of all types of capital. The complex regional balance consists of ecologicaleconomic, ecological-social and socio-economic components. Based on the language of algorithmic networks, a simulation model complex for sustainable balanced development of the region has been developed, on which a series of experiments has been run. The results obtained make it possible to focus on the preferential development of human capital and on the support of innovation as the preferred option for the transition to a model of sustainability and integrated regional balance.